Do financial conditions have a predictive power on inflation in Turkey? - Bulut, Umit (International Journal of Economics and Financial Issues, 2016)
This paper aims at examining the causal relationships between financial conditions and inflation in Turkey by employing quarterly data from 2005:Q1 to 2015:Q3. To this end, the paper, first, constructs a financial conditions index (FCI) in Turkey and observes that the FCI can considerably capture the developments in Turkey and in the world. Then, the paper follows unit root tests. Finally, the paper conducts the asymmetric causality test. The asymmetric causality test explores that the FCI and inflation have a predictive power on each other and thus presents valuable information to the Central Bank of the Republic of Turkey (CBRT). Eventually, upon its findings, the paper asserts that the FCI (i) should be updated periodically, (ii) should be extended with new financial variables, if necessary, and (iii) should be monitored carefully by the CBRT in order to achieve inflation targets.